Empowering student readers: Digital library development and literacy enhancement - Dellia Prita; Saputro Sigit Dwi; Faisal Rofik; Rosidah Lailatul (BIO Web of Conferences)
Increasing literacy skills among students through the use of digital technology is increasingly urgent. This is shown by the low reading literacy condition of Darul Mustofa Vocational School students. The contribution of this research is to develop digital libraries to increase students' reading literacy interest in schools and increase the role of digital libraries more effectively. This study is research into digital library development using the waterfall method. This method has seven stages: problem definition, analysis, design, development, testing, implementation, and maintenance. This method is widely recognized in the educational IT sector to address software development problems in schools. The system is tested using functional and usability testing. Functional testing using the black-box method includes verification of 80 system functions, while usability testing assesses ease of use, ease of learning, and user satisfaction. Test results show 100% success for all tested functions and a usability score of 95%, indicating that this system is very efficient, easy to use, and satisfying to users. This success shows that the Darul Mustofa Vocational School digital library is ready to support the educational process by providing better and easier access to various reading materials, which is expected to improve students' literacy skills. This digital library can be expanded in the future by adding more features or expanding to other schools.